God-given talent of Arkady Averchenko - Жиленко, Ірина Рудольфівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The present article, based on the collection of stories «A Dozen Knives in the Back of Revolution» by Arkady Averchenko, deals with artistic and stylistic means used by the author.There has been distinguished an «amazing talent» of the writer, who used vivid language rich in expressive and lucid vocabulary, bright and eloquent symbols. A wide use of artistic means used by Averchenko renders his collection of stories very emotional and varied. The satirist uses many antitheses, epithets, metaphors, repetitions, onomatopoeiae, dialogues, rhetorical questions, exclamatory sentences, etc. to depict how fast the whole post-revolutionary life was being destroyed in Russia.